(untitled) (Economics and region, 2021)
The author analyzes the main theories of management that are relevant for modern and administrative organizations. It was determined that the achievements of the scientific and classical school of management are advisable to use in the context of the COVID-19 pandemic, including such principles as division of labor, discipline, the need for interaction between the manager and subordinates, initiative and corporate spirit, unity of power, performance results, incentives and rewards workers. This will allow structuring all processes and relationships within the enterprise in order to achieve the set goals and in conditions of a high level of uncertainty. The work of researchers at the School of Human Relations and Behavioral Sciences served as the basis for the development of modern models of organizational development in the context of the spread of digital technologies and the digitalization of the economy. Since digital technologies both create new opportunities for the development of modern enterprises and create new challenges. It is the knowledge of the achievements of scientists and management practitioners that will allow a modern manager to ensure the sustainable development of enterprises.